2009
DOI: 10.1016/j.jfms.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to pleural effusion in cats: Markers for distinguishing transudates from exudates

Abstract: Classification of pleural effusion (PE) is central to diagnosis. Traditional veterinary classification has distinguished between transudates, modified transudates and exudates. In human medicine PEs are divided into only two categories: transudates and exudates. The aim of this study was to evaluate, in 20 cats presented with PE, paired samples of serum and pleural fluid for the following parameters: Light's criteria (pleural fluid lactate dehydrogenase concentration (LDHp), pleural fluid/serum LDH ratio, pleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
2
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 32 publications
2
63
2
1
Order By: Relevance
“…FIP fluids are frequently labeled 'modified transudates' based on their perceived lack of cellularity. However, they are inflammatory exudates in the purest sense and do not meet the established physical or physiologic criteria for a modified transudate (Zoia et al, 2009). Most FIP effusions contain a fair number of cells (500-5000/μL), including macrophages, neutrophils and a low proportion of lymphocytes.…”
Section: Analysis Of Effusionsmentioning
confidence: 99%
“…FIP fluids are frequently labeled 'modified transudates' based on their perceived lack of cellularity. However, they are inflammatory exudates in the purest sense and do not meet the established physical or physiologic criteria for a modified transudate (Zoia et al, 2009). Most FIP effusions contain a fair number of cells (500-5000/μL), including macrophages, neutrophils and a low proportion of lymphocytes.…”
Section: Analysis Of Effusionsmentioning
confidence: 99%
“…Light's criteria have been evaluated in the classification of feline pleural effusion . In a recent prospective study, pleural fluid LDH and pleural fluid/serum total protein ratio were found to be the most sensitive and specific markers when classifying pleural fluid as a transudate or exudate, although pleural fluid pH was not measured . Biochemical markers of sepsis have also been evaluated in dogs and cats with peritoneal effusion.…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…As many veterinary practices currently have dry chemistry analyzers available that are capable of measuring LDH activity, this analyte could be useful in practice, allowing early and more targeted treatment. Although some studies involving cats and dogs have already been published, a systematic, prospective study evaluating LDH activity (plus other criteria) in animal effusions, paying attention to the effects of testing interval, freezing, postmortem interval, and sample origin, has not been done.…”
Section: Introductionmentioning
confidence: 99%